Variabilidade do solo numa unidade de amostragem em solos de cascavel e de ponta grossa, Paraná - Alvarez V , Victor Hugo; Marcos Carraro , Ivo (Revista Ceres, 2025)
To study the soil variability within different plot size, two units of sampling were chosen, one in Cascavel (purple latosol (LR))and other in Ponta Grossa (red-yellow latosol (LVm), Paraná.